Knowledge, attitude, practices and perceived job stress among physical therapists in the Kingdom of Saudi Arabia during the COVID-19 pandemic: a cross-sectional study - Pakkir Mohamed, Shahul Hameed; Subbarayalu, Arun Vijay (Acta Biomedica Atenei Parmensis, 2022)
Aim: The objective of this study was to assess the level of knowledge, attitude and practice (KAP) and perceived job stress among physical therapists (PTs) during the COVID-19 pandemic in the Kingdom of Saudi Arabia (KSA). Methods: A cross-sectional study design was adopted; 300 PTs working within the KSA were randomly selected, and the KAP questionnaire was distributed through email using a Google form during the first quarter of 2022. The questionnaire consisted of demographic information, KAP, and perceived stress level at the job. Data analysis was carried out using SPSS 20.0. Results: Most PTs are knowledgeable about the management of COVID-19 patients, where their overall correct response to the items of the knowledge-related questionnaire was 87%. Most PTs had positive attitudes toward successful control of COVID-19 (83%) and took necessary precautions, such as frequent handwashing (97.2%) and adherence to the Centers for Disease Control & Prevention (CDC) guidelines (91.5%) during practice. The overall job stress level of the PTs was ’Moderate’ (76.5%). This study showed a significant association between the level of job stress experienced by the PTs and selected demographic variables. Conclusion: PTs have adequate knowledge, exhibit a positive attitude and adhere to CDC guidelines while managing patients during the COVID-19 pandemic. Most PTs are prone to moderate job stress while managing patients during the COVID-19 pandemic, and appropriate strategies must be devised to alleviate their job stress and improve their efficiency.